Pengaruh Stres Kerja dan Beban Kerja terhadap Kinerja Perawat Bunda Medical Center (BMC) Padang - Andre Nofrian Syaputra; Lidya Martha (JURNAL RISET MANAJEMEN (JURMA), 2024)
The research aims to determine the influence of work stress and workload on the performance of nurses at BMC Padang Hospital. This study employs a quantitative method. The population consists of 82 respondents who are nurses at BMC Padang Hospital. The sampling technique used is total sampling, resulting in a sample size of 82 respondents. Data analysis is conducted using multiple linear regression analysis with the assistance of SPSS for Windows version 23. The research findings indicate that work stress has a partial negative and significant effect on the performance of BMC Padang Hospital, while workload has a simultaneous negative and significant effect on employee performance at BMC Padang Hospital.